PEMANFAATAN APLIKASI DIGITAL DALAM MENANGANI BULLYING DAN MEDIA PENDIDIKAN KARAKTER (STUDI KASUS: APLIKASI BEJAKEUN SMP NEGERI 43 BANDUNG) - Rizal Rifa'i, Muhammad; Mahpudz, Asep; Sartika, Rika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Bullying is a negative behavior that frequently occurs in our surroundings; it also occurs in schools, which are supposed to be safe and comfortable places for children to pursue their education and develop their character. As times change, digital technology continues to advance to support the education system, making education engaging, relevant, and up-to-date. One example of this is the development of an app to address bullying cases in schools, which can also strengthen character education. Anti-bullying apps serve as a tool for addressing bullying cases that frequently occur in school settings; this makes technology increasingly essential for managing such incidents, particularly as a means of resolving bullying cases. The research method adopted for this study is a qualitative approach, chosen because this study aims to understand the situation regarding bullying at SMP Negeri 43 in Bandung, as well as the process of addressing bullying cases through the BEJAKEUN app. The results of this study indicate that the BEJAKEUN app has a positive impact on students, as evidenced by the decrease in bullying cases at SMP Negeri 43 in Bandung. Additionally, the BEJAKEUN app also contributes to the development of students’ character traits, such as courage and empathy.